Exploration of the Implementation and Innovative Methods of Quran Memorization in the Batam City Islamic Junior High School Environment - Syafrinal, Syafrinal (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to explore the implementation and innovative methods in the Quranic memorization program in the Integrated Islamic Junior High School (SMPIT) in Batam City. The background of the study is based on the increasing need for Islamic educational institutions to provide effective, adaptive, and relevant memorization learning models for the current generation. This study employs a qualitative approach with a case study design, focusing on four SMPITs in Batam City. The research subjects include 12 memorization teachers, four memorization coordinators, and 20 students, who serve as supporting informants. Data collection techniques were carried out through in-depth interviews, observation of the learning process, and analysis of memorization program documents in schools. Data were analyzed using Miles & Huberman's interactive analysis model, which involves data reduction, data presentation, and conclusion drawing. Data validity was strengthened through source triangulation and technique triangulation, resulting in credible findings. The results of the study indicate that the implementation of the tahfidz program was carried out systematically through memorization target planning, talaqqi deposits, muroja’ah reinforcement, and tiered evaluation. In terms of methods, a combination of traditional and innovative approaches is employed, including the use of digital media, audio-visual techniques, peer halaqah, and reward-based motivational strategies. All of these methods have been proven to improve the quality of memorization, motivation, and student engagement.